IMPROVING THE FINANCIAL SUSTAINABILITY OF TEXTILE ENTERPRISES - D.M., Mahkmudova (The journal of contemporary issues in business and government, 2021)
Process of development the strategy of financial stability includes definition of the most effective directions according to the solution of goals which is followed by search and an assessment of alternative versions of possible strategic financial decisions on criterion of increase in level of financial stability of enterprises of textile industry.